1991
DOI: 10.1111/j.1440-169x.1991.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunological Characterization of Collagenase in Tissues of Metamorphosing Bullfrog Tadpoles

Abstract: Tissue inhibitor of metalloproteinases (TIMP, a specific inhibitor of collagenase) was found to inhibit thyroid hormone-induced tail regression, suggesting the important role of collagenase in this process. Collagenase was purified from culture media of back skin of tadpole of bullfrog, Rana catesbeiana. Anti-tadpole collagenase polyclonal antisera were obtained against the purified enzyme. The antibody inhibited the activity of tadpole collagenase. The antisera reacted to tissues of adult bullfrogs, tadpoles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…The biological significance of the presence of TRE in anuran MMP1 is not clear at present. Our data support the hypothesis that a TRE in anuran MMP1 evolved to regulate the remodeling of larval tissue to adult during metamorphosis (Oofusa & Yoshizato 1991, 1996. Further works are required to determine whether other anuran MMPs contain TRE and if this observation extends to other vertebrates besides humans.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The biological significance of the presence of TRE in anuran MMP1 is not clear at present. Our data support the hypothesis that a TRE in anuran MMP1 evolved to regulate the remodeling of larval tissue to adult during metamorphosis (Oofusa & Yoshizato 1991, 1996. Further works are required to determine whether other anuran MMPs contain TRE and if this observation extends to other vertebrates besides humans.…”
supporting
confidence: 84%
“…We prepared specific antisera against Rana MMP1 and cloned its cDNA (Rmmp1) utilizing these antisera. The expression of MMP1 protein and Rmmp1 was greatly enhanced in bullfrog tadpoles during both T 3 -induced and spontaneous metamorphosis (Oofusa & Yoshizato 1991, Oofusa et al 1994. These studies support the notion that MMP1 is responsible for the extensive remodeling of anuran larval tissues taking place during metamorphosis (Yoshizato 1989).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using immunohistochemistry, Oofusa and Yoshizato (1991) found that bullfrog MMP1 protein increased in back skin in response to T 3 treatment. These results are interesting because skin from the tadpole trunk undergoes remodeling that is histologically similar to the remodeling observed in the current study (reviewed by Yoshizato, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MMP1 is a gene that is known to be directly targeted by TH in Rana catesbeiana (Oofusa and Yoshizato, 1996; Sawada et al, 2001). In R. catesbeiana, MMP1 is involved in collagen turnover that occurs during tail resorption and skin remodeling (Oofusa and Yoshizato, 1991). The functions of the rest of these genes (KRT6A, KRT14, GLUL, EMP1, CALM2) during amphibian metamorphosis are largely unknown.…”
Section: Methodsmentioning
confidence: 99%